PENGARUH FRAUD TRIANGLE FACTORS TERHADAP PERILAKU FRAUD - Taufiq Andre Setiyono (Among Makarti, 2019)
AbstractThe Fraud action is frequent and increase in many area. It brings a loss to firms and government. Many factors can affect Fraud, such as unsuitability of compensation, internal control ineffectiveness, and perceived behavioral control. This research aims to obtain empirical evidence abaout influence of unsuitability of compensation, internal control ineffectiveness, and perceived behavioral control on Fraud with intention to Fraud as an intervening variable.Population of this research is the civil servant in Tegal city as much as 564. The samples are 155 with purposive sampling technique type quota sample. The data of this research obtained were analyzed by using Partial Least Square (PLS). The data were processed by the SmartPLS3.0. software application.The result showed that internal control ineffectiveness and perceived behavioral control positive significantly affect to intention to Fraud, internal control ineffectiveness and perceived behavioral control also positive significantly affect to Fraud. But this research showed that unsuitability of compensation not significantly affect to intention to Fraud, and not significantly affect to Fraud. Intention to Fraud not significantly affect to Fraud. Direct effect between unsuitability of compensation, internal control ineffectiveness and perceived behavioral control to Fraud is more than indirect effect. It proves that the intention to Fraud is not the mediator in this research. Keywords :    unsuitability of compensation, internal control ineffectiveness, perceived behavioral control, intention to Fraud, Fraud.